Digital Economy Report 2024 - UN Trade; Development (United Nations, 2024)
The Digital Economy Report 2024 turns the attention to the environmental footprint of digitalization. The Report discusses environmental impacts along the life cycle of digital devices and information and communications technology infrastructure with regard to raw material extraction and processing, manufacturing, distribution; use and the end-of-life phase. The direct effects on natural resources, including transition minerals, energy and water, as well as greenhouse gas emissions and waste-related pollution can be said to constitute the “environmental footprint” of the ICT sector. There are also indirect environmental effects from the use of digital technologies and services in different sectors of the economy, and the Report includes a dedicated chapter on e-commerce. The report underlines the need to maximize the positive impact of digitalization while minimizing the negative impacts on environmental sustainability.